Open Court Principle for The Public in Material Judicial Review Right in The Supreme Court - Andryan Andryan (Jurnal Penelitian Hukum De Jure, 2022)
The Supreme Court (MA) has the authority legality review on regulations under the law against the law as stated in Article 34A paragraph (1) of the 1945 Constitution. Unlike the Constitutional Court (MK) in the examination process until the ruling applies Open Court Principle the Supreme Court does not implement it because apply the legal provisions that apply to the application case in the shortest possible time. This research uses normative legal research methods with conceptual approaches, philosophical approaches and statute approach. “There are two research questions of this study namely why is the principle of the trial open to the public in the right of judicial review in the MA in the concept of modern legal states and what is the constitutional basis for a trial open to the public based on the principle of Audi et Alteram Partem.? Based on principle as law country, Indonesia should emphasize on transparency to make public decision at court so that justice will prevail. The Supreme Court can make rule that accommodate the spirit of a trial that is open to the public as in the principle of Audi et Alteram Partem.